The Future of Human Resource Management in the Digital Era: A Review of Public Enterprises - Muzanenhamo, Arvid; Rankhumise, Edward Malatsi (Contemporary Issues of Business and Management: The Proceedings of the \(10^{th}\) International Conference on Business and Management Dynamics (ICBMD), Edition 1, 2025)
In recent years, the world has been experiencing digital changes referred to as the fourth industrial revolution. This led to the introduction of technological innovations which intensely modified various aspects of modern life. Public sector organisations also play a major role in this revolution. However, public enterprises face challenges related to digital transformation, such as employee resistance, bureaucratic structures, regulations, and the changing political culture. This paper made use of UTAUT model to address major missing links in people management and organisational development of public enterprises in the digital era. This study used the document analysis technique and analysed previous research papers from Web of Science, Scopus, Taylor and Francis and Google Scholar on human resource digitisation in public enterprises. This guided the study to consciously select only papers on Human Resource Management (HRM) and digitisation. The study revealed that artificial intelligence training, managerial autonomy and external coordination are crucial aspects of state-owned enterprises in the digital era. This helps public enterprises to quickly adjust to new innovations and obtain a competitive advantage. The results provide managers in SOEs with a modernised overview of research in the HRM field in the context of digitalisation, including future research directions.